2011
DOI: 10.1002/jsfa.4502
|View full text |Cite
|
Sign up to set email alerts
|

Whey protein–polysaccharide blended edible film formation and barrier, tensile, thermal and transparency properties

Abstract: Whether properties of PS-WPI blended films are intermediate to properties of the pure PS and WPI film depends on the particular PS and specific property. In the case of MC or HPMC with WPI, the blended films reflect the higher TS of the PS and lower OP of the WPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(92 citation statements)
references
References 42 publications
(47 reference statements)
4
83
1
4
Order By: Relevance
“…The thermograms of DSC analysis and the related peak temperatures were given and illustrated in Figure 3. It was reported that the first endothermic events were glass transition, followed by an endotherm associated with the melting of the ordered structures [20,49]. As observed in Figure 3, the value of the pure collagen film (55.63 ∘ C) is inferior to CS1 (85.31 ∘ C), CS2 (103.71 ∘ C), and CS3 (80.71 ∘ C).…”
Section: Thermal Propertiesmentioning
confidence: 81%
“…The thermograms of DSC analysis and the related peak temperatures were given and illustrated in Figure 3. It was reported that the first endothermic events were glass transition, followed by an endotherm associated with the melting of the ordered structures [20,49]. As observed in Figure 3, the value of the pure collagen film (55.63 ∘ C) is inferior to CS1 (85.31 ∘ C), CS2 (103.71 ∘ C), and CS3 (80.71 ∘ C).…”
Section: Thermal Propertiesmentioning
confidence: 81%
“…Meanwhile, these films could inhibit lipid oxidation in food systems due to their significant oxygen barrier ability (Hosseini, Javidi, & Rezaei, ). Yoo and Krochta () listed several studies which show that edible films produced from a combination of biopolymers including gelatin and chitosan have better mechanical properties than single component films and will, therefore, be applied in our study. Gelatin can be mixed with other polymeric molecules for the fabrication due to reactive groups, for example, NH2, COOH, and OH (Hosseini & Gómez‐Guillén, ).…”
Section: Introductionmentioning
confidence: 99%
“…Pure HPC films represented the highest E % values not only because of the glucopyranosyl units that stabilize it, but also because of the intermolecular hydrogen bonds formed by numerous hydroxyl groups (Yoo & Krochta, ). Owing to the presence of intermolecular hydrogen bonding, the films fabricated by simplex KF exhibited higher TS values than films by pure HPC ( p < .01; B. Li et al., ).…”
Section: Resultsmentioning
confidence: 99%